Respuesta :

Answer:

[tex]d = \frac{y - 5a}{5 + 6c}[/tex] if 5 + 6c is not 0.

Step-by-step explanation:

-5d + y = 6dc + 5a

first let's move all d's to one side and the rest to the other

-5d -6dc = 5a - y

5d + 6dc = y - 5a

d(5 + 6c) = y - 5a

if (5 + 6c) isn't 0:

[tex]d = \frac{y - 5a}{5 + 6c}[/tex]

Answer:

d = [tex]\frac{y-5a}{5+6c}[/tex]

Step-by-step explanation:

Given

- 5d + y = 6dc + 5a ( subtract 6dc from both sides )

- 5d - 6dc = 5a - y ← factor out - d from each term on the left

- d(5 + 6c) = 5a - y ( multiply through by - 1 )

d(5 + 6c) = y - 5a ← divide both sides by (5 + 6c)

d = [tex]\frac{y-5a}{5+6c}[/tex]